The Advertising Market and the Evolution of the WEB: a study about the company Rock Content - Souza, Juliana Lopes de Almeida; Ribeiro de Matos, Marco Túlio; Campos, Rodrigo Parreiras; Patrocinio, Rachel Farias do (Archives of Business Research, 2018)
The article aims to study and understand the tools available on the web and relate these tools to the concept of digital marketing, introducing new ways of business, through the creative economy and entrepreneurship. The methodological procedure chosen for the investigation of this work was the exploratory research. The research was developed through the qualitative method, with interviews as instrument of data collection. The type of research technique was classified as semi-structured interview, in which communication professionals in the company Rock Content answered a questionnaire, with a view to obtaining previously information about the demands of the advertising market, the difficulties and the challenges encountered in the daily life of these professionals. In this perspective, the present study discusses concepts raised by the literature on the web and entrepreneurship, insofar as this scenario of the advertising market in the web is analyzed.